Comprehensive analysis of Brassica napus Glycosyl hydrolase family 1 genes and functional analysis of BnaBGLU27.C08 in clubroot resistance - Yiji Shi; Xiang Liu; Shunjun Bao; Ye Li; Yuqing Shi; Chen Liang; Hongyu Sha; Zihao Yu; Qing Su; Xiyu Zhang; Xiaoyan Li; Weinan Sun; et al. (BMC Genomics)
Abstract Background β-Glycosidases (BGLUs), belonging to the Glycoside Hydrolase Family 1 (GH1), play crucial roles in plant growth, development, and stress adaptation. While BGLUs have been extensively characterized in various plants, a comprehensive analysis of the BGLU family in Brassica napus has yet to be conducted. Results In this study, we identified 131 BnaBGLU genes in B. napus and classified them into 11 subfamilies. Gene duplication analysis revealed that the expansion of the BnaBGLU family primarily resulted from segmental duplications. Structural analysis revealed high conservation within subfamilies, while promoter cis-element profiling and transcriptional studies under phytohormone treatments and abiotic stresses demonstrated BnaBGLUs respond to diverse environmental stimuli. Additionally, BnaBGLUs exhibit tissue-specific expression patterns. Notably, BnaBGLU27.C08 was significantly upregulated 96 h post-inoculation with Plasmodiophora brassicae in the root of clubroot-resistant (CR) B. napus varieties. Furthermore, overexpression of BnaBGLU27.C08 in Arabidopsis significantly enhanced resistance to clubroot disease. Conclusions These findings establish a foundation for further investigation on the BnaBGLU family in B. napus and offer potential candidate genes for breeding CR B. napus varieties.